Opening access to administrative data for evaluating public services: The case of the Justice Data Lab. (April 2015) - Lyon, Fergus; Gyateng, Tracey; Pritchard, David; Vaze, Prabhat; Vickers, Ian; Webb, Nicola
As government administrative data sets are increasingly made available for new (non-administrative) purposes, there is a need to improve access to such resources for voluntary and community organizations, social enterprises and private businesses for statistical analysis and evaluation purposes. The Justice Data Lab set up by the Ministry of Justice in the UK presents an innovative case of how administrative data can be linked to other data held by organizations delivering public services. The establishment of a unit within a secure setting holding evaluation and statistical expertise has enabled providers of programmes aimed at reducing re-offending to obtain evidence on how the impact of their interventions differs from that of a matched comparison group. This article explores the development of the Justice Data Lab, the methodological and other challenges faced, and the experiences of user organizations. The article draws out implications for future development of Data Labs and the use of administrative data for the evaluation of public services.